Learning from moderation of OTJs: The political balancing act. - Poskitt JM (My University)
Internationally, attention to educational accountability sharpened during the Global Financial Crisis period, with a political need for student achievement data. International achievement testing strongly influenced educational policy globally (Volante, 2016) and in New Zealand (Poskitt, 2016a). “Advocates of standards-based reform argue that large-scale assessment programs provide valuable and necessary information to assist in the revision of national evaluation systems, curriculum standards, and performance targets” (Volante, 2016, p.3). Worldwide testing programs provide international and intra-national comparative data on student achievement at particular student ages, but they do not capture achievement across all year levels of compulsory schooling. Limited sampling size and the need for international comparability in content means the tests have reduced validity for local contextual purposes. To address the need for localised student achievement data across the primary school years, New Zealand implemented National Standards (NS) in 2010. The intention of NS was also to avoid risks of narrowing the curriculum and ‘teaching to the test’ by developing NS that were broad in description, linked to New Zealand Curriculum levels and utilized teachers’ professional judgments (Poskitt, 2016b). At the heart of the NS policy are overall teacher judgments (OTJs). Primary teachers are required to make standards judgments for each of their students in reading, writing and mathematics based on a range of achievement information. Schools vary in the ‘evidence’ they use and their interpretations of it. Social moderation is intended to assist the dependability of the OTJs. “This practice involves teachers expressing their interpretations of assessment criteria and standards with the aim of reaching agreement on the award of a standard” (Klenowski & Wyatt-Smith, 2014, p.74), and thereby increase the validity and reliability of teachers’ subsequent judgements. Little is known about the moderation processes used by New Zealand teachers. In what ways do teachers express their interpretations of assessment criteria and standards? What influences their judgments in moderation meetings? This paper examines the moderation conversations of teachers involved in a school cluster professional development initiative on student writing. Political influences are evident in relation to the power of: teacher knowledge and expectations, seniority (by age and designation), reference points used and limited resourcing. Unless resources are invested in ongoing professional learning for moderation, dependability of OTJs will be undermined. The resultant risk is political influences will usurp teacher involvement in assessment and rely primarily on international achievement tests for monitoring the health of NZ’s education system.
Keywords: National Standards; Social moderation; Overall teacher judgments